Analysis of The Effectiveness and Challenges of Using TikTok to Improve EFL Students’Listening - Riska Alviani; Dzul Rahman; Khusnul Khatimah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
The extensive utilization of social media in educational settings has heightened academic interest in its instructional potential, especially within the domain of English as a foreign Language (EFL). TikTok has garnered attention for its short form video format, which is thought to offer genuine language input and captivating listening exposure. Nevertheless, current research frequently highlights favorable results without adequate critical assesment. This study seeks to investigate the conditional efficacy of TikTok in enhancing EFL students listening abilities, while also analyzing learners perspective and the problems they face. A sequintal explanatory mixed-methods design was utilized. Quantitative data were collected via questionnaires administered to 57 undergraduate EFL students to ascertain broad trends in perceptions and experiences. To augment these findings, qualitative data were gathered via semi-structured interviews with a select group of participants, facilitating a more profound examination of individual perspectives. The data were examined utilizing descriptive statistic and thematic analysis. The findings indicate that students predominantly possess fairly favorable views of TikTok, especially regarding exposure to diverse English dialects, enhanced learning motivation, and adaptable access to auditory resources. Nevertheless, other questionnaire items exhibited indifferent replies, signifying that students learning experiences were not consistenly favorable.